Thermoset resins for composites : directory & databook - Starr, Trevor F. (Woodhead Pub., 1998)
This second edition has been compiled to take account the continued expansion of the composites industry. Additional entries cover new companies, products and resin systems, which have appeared on the market since the 1st edition. A change in the lay-out of part two allows more property tabulation and more descriptive entries for resins.